Literature Review : Jamblang (Syzygium Cumini (L): A Review Of Its Bark And Medicinal Uses - Eka Sevianti; Himyatul Hidayah; Abdul Aziz; M Alvian Noordiansyah (Jurnal Ilmiah Wahana Pendidikan, 2023)
The use of plants as medicine in Indonesia has been known and used for thousands of years, but until now their use has not been properly recorded. The aim of this study was to identify secondary metabolites found in the stems of jamblang or juwet rice (Syzygium cumini L) bark. The research design used in this study is (LRA) literature review article. The results obtained from this jamblang plant (Syzygium Cumini (L) found Tannins, Carbonhydrates, Vitamin C, Polyphenols, β - Carotene, Flavanoids, Alkaloids, Terpenoids, Steroids, Beta Sitosterol Compounds, Betulinic Acid, Eugenin, Quercetin, Campherol and so on. which can be used as traditional medicine both from fruit, leaves, bark and others